Analysis of cracked lap shear testing of tungsten-CFRP hybrid laminates. (15th April 2017) - Jokinen, J.; Kanerva, M.
Graphical abstract: Highlights: We simulated the delamination process in hybrid CLS fracture test specimens. Due to residual stresses, the visual detection of crack onset can be invalid. The invalidity of the CLS method depends on the lay-up and cure of hybrid specimens. For the W-CFRP interface, we determined Gcr = 261 J/m 2 at ψ = 71.8°. Abstract: In this work, we studied the effects of residual stresses on the testing of a cracked lap shear specimen (CLS). The analysis focused on tungsten-CFRP laminates for radiation protection applications. A 3-D finite element model was generated and the virtual crack closure technique (VCCT) was applied to determine fracture toughness. Crack propagation was analyzed using cohesive zone modelling (CZM) to combine multiple strain gauge data from experiments and the information from the VCCT. Our analysis indicated that residual stresses cannot be ignored in a valid analysis of tungsten-CFRP hybrid laminates—the experimentation with hybrid CLS specimens requires numerical crack simulation.